The practice of applying the norms on responsibility for sexual crimes (Articles 131-135 of the Criminal Code of the Russian Federation) and ways to improve it - A. A. Bimbinov (Правоприменение)
The subject. The article reflects the progress and results of the study of the practice of applying the norms on responsibility for crimes against sexual inviolability and sexual freedom of the individual (Chapter 18 of the Criminal Code of the Russian Federation). There are a large number of general and specific law enforcement problems that do not allow us to effectively counteract such crimes.Purpose of the study. The purpose of the study is to confirm the scientific hypothesis about the presence of systemic problems in the practice of applying the norms of Chapter 18 of the Criminal Code of the Russian Federation, as well as to develop proposals for improving law enforcement.Methodology. The identification of law enforcement problems was carried out by analyzing published and unpublished materials of judicial practice and comparing them with the main categories and principles of criminal law. Access to the published materials was carried out through the legal reference systems and the State Automated System "Justice". Unpublished materials were obtained in the course of their own professional activities, as well as when studying the scientific works of other authors. The use of previously obtained results of their own scientific activities, the results of scientific research of modern criminologists and criminologists, as well as the study of the experience of foreign countries allowed us to formulate proposals for solving the identified problems.The main results. In the course of the study, the following systemic problems of law enforcement were identified. (1) The uncertainty of the content of other sexual actions. (2) The ambiguity of the legal assessment of the multiplicity of crimes against sexual inviolability and sexual freedom of the individual. (3) The blurring of the content and methods of committing depraved actions.These problems characterize the current state of the practice of applying the norms of Chapter 18 of the Criminal Code of the Russian Federation.To solve these problems and improve law enforcement, the following proposals are justified and formulated.At the level of the resolution of the Plenum, it should be clarified that other actions of a sexual nature are contact forms of the perpetrator's influence on the victim's body that can satisfy sexual needs, with the exception of sexual intercourse, sodomy and lesbianism (for example, masturbation, fellatio, forced kisses, manual influence on the mammary glands or genitals and other ways of stimulating sexual arousal).On the issue of the qualification of continuing crimes, the Plenum of the Supreme Court should indicate that repeated sexual acts that form the objective side of one corpus delicti should be considered as a single continuing crime, if their commission was covered by a single intent. At the same time, such intent may be evidenced by the behavior of the perpetrator, in which he does not stop the violation of sexual freedom or sexual inviolability of a particular victim.The provisions of the resolution of the Plenum of the Supreme Court concerning the qualification of depraved acts should be changed, indicating that depraved acts are other sexual acts that are not covered by the dispositions of Article 134 of the Criminal Code of the Russian Federation, and actually depraved acts committed without direct physical contact in order to satisfy sexual needs or arouse the victim's interest in sexual acts. It is also important to emphasize that the acts provided for in the note to Article 131 of the Criminal Code of the Russian Federation should include only other actions of a sexual nature.Conclusions. In conclusion, it should be noted that the proposals formulated to solve the identified problems of law enforcement cannot completely eliminate them. The solution to these problems should be found through legislative changes. In this activity, it seems correct to focus on the positive experience of European legislators, which provides for a more detailed differentiation of responsibility depending on the features that objectively affect the nature and degree of public danger of the act.